Disease and treatment characteristics do not predict symptom occurrence profiles in oncology outpatients receiving chemotherapy. Issue 15 (2nd May 2014) - Miaskowski, Christine; Cooper, Bruce A.; Melisko, Michelle; Chen, Lee‐May; Mastick, Judy; West, Claudia; Paul, Steven M.; Dunn, Laura B.; Schmidt, Brian L.; Hammer, Marilyn; Cartwright, Frances; Wright, Fay; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND A large amount of interindividual variability exists in the occurrence of symptoms in patients receiving chemotherapy (CTX). The purposes of the current study, which was performed in a sample of 582 oncology outpatients who were receiving CTX, were to identify subgroups of patients based on their distinct experiences with 25 commonly occurring symptoms and to identify demographic and clinical characteristics associated with subgroup membership. In addition, differences in quality of life outcomes were evaluated. METHODS Oncology outpatients with breast, gastrointestinal, gynecological, or lung cancer completed the Memorial Symptom Assessment Scale before their next cycle of CTX. Latent class analysis was used to identify subgroups of patients with distinct symptom experiences. RESULTS Three distinct subgroups of patients were identified (ie, 36.1% in Low class; 50.0% in Moderate class, and 13.9% in All High class). Patients in the All High class were significantly younger and more likely to be female and nonwhite, and had lower levels of social support, lower socioeconomic status, poorer functional status, and a higher level of comorbidity. CONCLUSIONS Findings from the current study support the clinical observation that some oncology patients experience a differentially higher symptom burden during CTX. These high‐risk patients experience significant decrements in quality of life. Cancer 2014;120:2371–2378. © 2014 American Cancer Society.